KONSTRUKSI MAKNA HIJRAH BAGI ANGGOTA KOMUNITAS LET’S HIJRAH DALAM MEDIA SOSIAL LINE - Ditha Prasanti; Sri Seti Indriani (Institut Agama Islam Negeri Kendari, 2019)
Hijrah has different meanings for members of Let's Hijrah community. This Islamic community calls its community as Let's Hijrah according to its hopes and goals in life to lead them to a better life change. In this study, the writer investigatd the construction of the meaning of Hijrah itself for members of Let's Hijrah community in social media LINE. This community provides all kinds of information and monitors all its activities through LINE's social media group account. Thus, the process of communication that exists was more dominant in the LINE social media accounts. The author used a qualitative approach to explaining this research. The results of this research had shown that the construction of the meaning of hijrah for the members of Ler's Hijrah community in LINE social media consists of: (1) Hijrah is agreed as the purpose of life to make a change to a better thing according to the teachings of Islam; (2) Hijrah must be demonstrated in both verbal and non-verbal contexts by every member of Let's Hijrah community; (3) Hijrah is also interpreted as the formation of each member's identity in the community of Let's Hijrah.